Joy and Pain: An Affect Studies Perspective on Natural Birth Films - Rudrum, Sarah (Atlantis, 2013)
This paper uses discussions of pain, shame, and joy within critical affect studies to exam-ne two documentaries, The Business of Being Born (2008) and Orgasmic Birth (2008). It argues that, despite its valuable contributions, natural childbirth discourse conveys a troubling message, one that insists on joy over pain, advocates choice rather than systematic change, and perpetuates a problematic dichotomy between “natural” and “medical” birth.